NHS Health Check and healthy lifestyle in Leicester, England: analysis of a survey dataset. (January 2020) - Chattopadhyay, K; Biswas, M; Moore, R
Aims: A major component of the National Health Service (NHS) Health Check in England is to provide lifestyle advice to eligible participants. The aims of the study were to explore the variations (in terms of uptake) in the NHS Health Check in Leicester and to determine its association with a healthy lifestyle. Methods: This cross-sectional study used data from the Leicester Health and Wellbeing Survey (2015). Results: The odds of having an NHS Health Check were found to be higher in Black and minority ethnic groups and in people of other religions. The odds were lower in people without a religion, residing in the fourth index of multiple deprivation quintile and in ex-smokers. No associations were found between having an NHS Health Check and describing a healthy lifestyle, following a healthy lifestyle, thinking of making lifestyle changes in the next 6 months, cutting down on/stopping smoking among current smokers, or amount of alcohol current drinkers would like to drink. Conclusions: In Leicester, a few variations in having an NHS Health Check were found among different socio-economic, demographic and behavioural groups. No association was found between the NHS Health Check and a healthy lifestyle. Thus, the improvement work should focus on reducing these variations in having the NHS Health Check and bringing its benefits on promoting a healthy lifestyle.